JANGAN MENJADI SERUPA DENGAN DUNIA DIGITAL: TELAAH KITAB ROMA 12:2 DALAM BUDAYA ALGORITMA - Stefanus Padan (STAK Reformed Remnant Internasional, 2026)
This article examines Romans 12:2 in relation to contemporary algorithmic culture. Previous studies in digital theology have generally focused on the use of technology in church ministry, but few have connected Romans 12:2 with algorithmic culture as a system shaping human thought patterns. This study aims to analyze the exegetical meaning of Romans 12:2 and its relevance in the modern digital context. Using a qualitative-exegetical library research method, the study analyzes the Greek text and engages digital culture studies. The findings show that algorithms function as modern structures of conformity through personalization, echo chambers, and digital social validation. Romans 12:2 offers a biblical framework to respond through the renewal of the mind as the basis for spiritual discernment. This study contributes to the development of digital theology and opens opportunities for further empirical research.